THE THOUGHT OF EDUCATION REFORMATION OF NGUYEN TRUONG TO AND ITS SIGNIFICANCEIN EDUCATION RENOVATION IN VIETNAM TODAY - Thu Hien, Bui Thi (International Journal of Psychosocial Rehabilitation, 2024)
Nguyen Truong To was one of the initiations of the country’s reform trend in Vietnamin the late nineteenth century. His systematic and comprehensive reform proposals cover allareas of social life; in it, he paid much attention to education reform. His reform ideas reflect anew vision and thinking to meet the requirements of national history, protection of sovereigntyand national development. The article clarifies the content of educational reform ideology ofNguyen Truong To, from which we draw some implications for the cause of educationalinnovation in Vietnam nowadays.